IMPLEMENTASI MODEL PROJECT BASED LEARNING UNTUK MENINGKATKAN MOTIVASI DAN PRESTASI BELAJAR PADA SISWA KELAS IV SD N 2 SABDODADI - WAHYUNI WAHYUNI (ACTION : Jurnal Inovasi Penelitian Tindakan Kelas dan Sekolah, 2022)
This research is motivated by students' difficulties in understanding the material about Natural Sciences. Based on this, the use of the Project Based Learning model is expected to improve students' ability to solve questions about energy sources for class IV at SD Negeri 2 Sabdodadi. This research is a Classroom Action Research (CAR). The subjects in this study were fourth grade students of SD Negeri 2 Sabdodadi. The object of this research is the use of the Project Based Learning model to improve understanding of the content of science lessons. This research was conducted in 2 cycles. Each cycle consists of planning, implementation, observation, and reflection. The cycle is stopped when the indicators of research success have been achieved. Data collection methods used in this study were observation, questionnaires, and tests. Research instruments in the form of observation sheets, questionnaires and test questions. Data analysis used qualitative and quantitative data analysis. The results showed that the use of the Project Based Learning model could improve students' understanding of the content of the fourth grade science lesson at SD Negeri 2 Sabdodadi. This can be seen from the results of the learning completeness pre-cycle with an average value of 30%. After the action was taken using the Project Based Learning model, the results of the first cycle of research were complete learning with an average value of 50%. The results of the second cycle of study completeness study with an average value of 80%. ABSTRAKPenelitian ini dilatarbelakangi oleh kesulitan siswa dalam memahami materi tentang Ilmu Pengetahuan Alam. Berdasarkan hal tersebut, penggunaan model Project Based Learning diharapkan dapat meningkatkan kemampuan siswa dalam menyelesaikan soal tentang sumber energi kelas IV di SD Negeri 2 Sabdodadi. Penelitian ini merupakan Penelitian Tindakan Kelas (PTK). Subjek dalam penelitian ini adalah siswa kelas IV SD Negeri 2 Sabdodadi. Objek dalam penelitian ini adalah penggunaan model Project Based Learning untuk meningkatkan pemahaman muatan pelajaran IPA. Penelitian ini dilakukan sebanyak 2 siklus. Setiap siklus terdiri dari perencanaan, pelaksanaan, observasi, dan refeksi. Siklus dihentikan apabila indikator keberhasilan penelitian telah tercapai. Metode pengumpulan data yang digunakan dalam penelitian ini adalah observasi, angket, dan tes. Instrument penelitian berupa lembar observasi, angket dan soal tes. Analisis data menggunakan analisis data kualitatif dan kuantitatif. Hasil penelitian menunjukkan bahwa penggunaan model Project Based Learning dapat meningkatkan pemahaman siswa dalam muatan pelajaran IPA kelas IV SD Negeri 2 Sabdodadi. Hal ini dapat diketahui dari hasil prasiklus ketuntasan belajar dengan nilai rata-rata 30%. Setelah dilakukan tindakan dengan menggunakan model Project Based Learning hasil penelitian siklus I ketuntasan belajar dengan nilai rata-rata 50%. Hasil penelitian siklus II ketuntasan belajar dengan nilai rata-ataa 80 %.